Solving arithmetic problems in first and second language: Does the language context matter?. (April 2016) - Van Rinsveld, Amandine; Schiltz, Christine; Brunner, Martin; Landerl, Karin; Ugen, Sonja
Abstract: Learning mathematics in a second language is a challenge for many learners. The purpose of the study was to provide new insights into the role of the language context in mathematic learning and more particularly arithmetic problem solving. We investigated this question in a German–French bilingual educational setting in Luxembourg. Participants with increasing bilingual proficiency levels were invited to solve additions in both their first and second instruction languages: German and French. Arithmetic problems were presented in two different conditions: preceded by a semantic judgment or without additional language context. In the French session we observed that additions were systematically performed faster in the condition with an additional language context. In contrast no effect of the context was observed in the German session. In conclusion, providing a language context enhanced arithmetic performances in bilinguals' second instruction language. This finding entails implications for designing optimal mathematic learning environments in multilingual educational settings. Highlights: Learning math in a second language is a challenge for many learners. Bilingual learners solved additions in two different language context conditions. Language context improved arithmetic performances during second language sessions.